Globalization East and West - Turner, Bryan S.; Khondker, Habibul Haque (Sage, 2010)
"Do we confuse globalization for Americanization? What are the distinctive elements in the interplay of the local and the global?This much needed book is the first full length text to examine globalization from the perspective of both the West and the East. It considers globalization as a general social and economic process, and the challenges it presents for Western social science. The meaning of a global perspective is explored through various concrete examples: religion, migration, medicine, terrorism, global disasters, citizenship, multiculturalism, media and popular culture. Introduced with a forward from Roland Robertson the book is brimming with novel interpretations and fresh insights that will contribute to illuminating the practical realities of globalization."-Provided by publisher.